مُلاءَمة الألغوريتمات الوراثية لاستخدامها في الجدولة الزمنية لمشروعات التشييد - الدياب علي; علي حمزة; زعرور نسيب (Latakia University Journal -Engineering Sciences Series, 2019)
تُعتبر نظرية الألغوريتمات الوراثية من أفضل و أحدث الطرق الرياضية المستخدمة في إيجاد الحل الأمثل للمسائل ذات الحلول الكبيرة العدد. إن مسألة الجدولة الزمنية هي من أهم المسائل في الإدارة الهندسية التي تحتمل العدد الكبير جداً من الحلول، إذ يُطلب إيجاد تسلسل تنفيذ العمليات (النشاطات) لمشروع ما مع مراعاة قيود الأسبقية و الموارد القابلة للتجدد، و من دون تغيير في مدد العمليات أو تقسيمها أو تغيير الموارد القابلة للتجدد اللازمة لها، بحيث يتم الحصول على الجدول الزمني الأقصر لمشروع التشييد. وهذا البحث يعنى بمُلاءَمة الألغوريتمات الوراثية لكي تصبح قادرة على حل المسألة المذكورة أعلاه ، إذ يتم التعبير عن مكونات مسألة الجدولة الزمنية بنماذج المفتاح العشوائي. The genetic algorithms theory is considered one of the best and newest mathematical methods being used to find the optimal solution to problems that have a great number of solutions. The scheduling problem is one of the most important problems in engineering management that has a variety of solutions, where the request is to find the sequence of executing the tasks (activities) of a project, taking precedence and renewable resources constraints into account, without changing the duration of the tasks or splitting them or changing the renewable resources needed for the tasks in order to get the shortest schedule for the construction project. This paper is concerned with fitting genetic algorithms in order to be capable of solving the problem mentioned above, where the construction project scheduling problem components are expressed by random key types.